Socioeconomic Factors and Educational Aspirations in Northern Nigeria: Islamic Endowment as a Possible Solution - Adamu Abubakar Muhammad; Hamza Abubakar Hussaini; Zuwaira Jibril Muhammad; Shafa’atu Ahmad Aliyu (CV Media Inti Teknologi, 2024)
The study aims to investigate the socioeconomic determinants that influence educational ambitions in Northern Nigeria and the potential role of Islamic waqf (Waqf). This research uses a qualitative approach. Expert interviews, case studies, and literature reviews are all incorporated into this technique. These techniques make it possible to understand the difficulties facing the local education system in great detail, as well as the historical and current contributions that Waqf has made to the advancement of education. The results of the analysis of the relevant theoretical framework and practical investigations yielded valuable insights into the ways in which the Islamic waqf system can close the huge educational gaps and inequalities in the area. The study looks at the relationship between socioeconomic status and educational goals in Northern Nigeria and how the use and revitalization of Waqf institutions can advance education in the area. The conclusion of the study is that in Northern Nigeria, socioeconomic factors are still a challenge to the desire to get an education. By involving collaboration between governments, businesses, and religious institutions to create effective and inclusive structures, Islamic waqf can be a potential solution to overcome socio-economic barriers in education.